Mental Accounting, Self Control, Self Efficacy dan Evaluasi Emotional Value : Bingkai Makna Kebahagiaan Tersembunyi Pasca Pembelian - Rendi Ardika (Jurnal Penelitian Ekonomi Akuntansi, 2023)
This study aims to understand financial treatment in the application of mental accounting related to self-control and self-efficacy. This reality often occurs in life but has not been balanced with emotional value evaluation to find the meaning of happiness. This study used the literature review method to take the 25 most relevant articles. The meaning of happiness depends on one's conception in describing it. This conception provides a frame that a person is happy with every decision he makes. Whether it's just to be happy born or even both. Self-love and self-rewarding emphasize happiness from someone's birth side. However, the addition of spiritualism in carrying out actions forms inner and outer happiness because happiness is formed by serving God.